A seed crystal bonding method for growing an aluminum nitride crystal
Patent Information
- Application Number
- CN202310536263.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-12
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2043-05-12
Smart Images

Figure CN116590794B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of semiconductor material preparation technology, and specifically to a seed crystal bonding method for aluminum nitride crystal growth. Background Technology
[0002] Aluminum nitride (AlN) is an ultra-wide bandgap semiconductor material with great application potential, boasting a bandgap of ~6.2 eV. It also exhibits high breakdown field strength, high saturated electron drift velocity, and excellent thermal conductivity and radiation resistance, making it the optimal substrate material for ultraviolet / deep ultraviolet LEDs and an ideal substrate material for GaN power devices. Physical vapor transport (PVT) is one of the most successful methods for preparing high-quality AlN bulk single crystals. However, the PVT method requires extremely high growth temperatures, exceeding 2200℃ for high-quality growth, making the process challenging, resulting in poor crystal growth stability and a tendency to produce low-quality crystals. Therefore, the bonding and fixing method of the seed wafer is crucial.
[0003] Because PVT crystal growth is performed at extremely high temperatures, the back side of the AlN seed wafer is prone to sublimation. Gaps between the seed wafer and the support components allow gas to backflow into the crystal, leading to internal voids and defects. This severely degrades crystal quality and reduces production yield. Currently, commonly used seed wafer fixing methods include chemical bonding and mechanical bonding. Methods to suppress voids include bonding, coating, and physical coating. Chemical bonding is a common method for semiconductor crystal growth, offering advantages such as simple processing and high operability. However, existing chemical adhesives used for AlN crystal growth are not resistant to temperatures exceeding 2200℃ and still easily generate pores during crystal growth. Mechanical bonding offers high stability and is less prone to detachment, but limitations in the processing precision of the support components can easily lead to gaps and internal voids. Coating is a common method to suppress back-side sublimation of the seed wafer, but the thin film is prone to detachment and cracking at the high temperatures of AlN crystal growth, failing to provide adequate protection. Therefore, there is an urgent need to develop a seed wafer bonding and fixing method that is highly stable, heat resistant, and can effectively suppress the formation of voids, thereby effectively reducing or even eliminating void defects, improving crystal quality, and increasing the production yield of AlN substrates. Summary of the Invention
[0004] The purpose of this invention is to provide a seed crystal bonding method for aluminum nitride crystal growth that is extremely resistant to high temperatures (>2200℃).
[0005] The present invention is achieved through the following technical solution.
[0006] A method for bonding seed crystals during aluminum nitride crystal growth includes the following steps:
[0007] S1: Mix aluminum nitride powder, silicate, tungsten powder and distilled water in a certain proportion to make an adhesive;
[0008] S2: Apply the adhesive evenly to the bonding surfaces of the support component and the AlN seed wafer respectively;
[0009] S3: Expose the adhesive on the bonding surface of the support component coated with adhesive and the AlN seed wafer, and bake at low temperature for a period of time;
[0010] S4: Place the bonding surface of the AlN seed wafer on the bonding surface of the support component;
[0011] S5: Place the bonded AlN seed wafer and support components under a certain negative pressure and at room temperature in a vacuum for a period of time;
[0012] S6: Place the bonded AlN seed wafer and support component into a high-temperature furnace, heat it in an inert gas atmosphere for a period of time, and slowly cool it to room temperature. Finally, the AlN seed wafer and support component are firmly bonded together.
[0013] Preferably, in step S1, the aluminum nitride powder has a particle size of 0.5-20 μm, and the tungsten powder has a particle size of 1-50 μm.
[0014] Preferably, in step S1, the weight percentage of aluminum nitride powder is 10-20%, the weight percentage of silicate is 1-5%, the weight percentage of tungsten powder is 40-70%, and the weight percentage of distilled water is 10-50%.
[0015] Preferably, in step S2, the support component can be made of any one of the following high-temperature resistant materials: tungsten, tantalum, molybdenum, tungsten carbide, tungsten nitride, tantalum carbide, tantalum nitride, and boron nitride.
[0016] Preferably, in step S2, the bonding surface of the support component is ground or polished, and the bonding surface of the AlN seed wafer is chemically and mechanically polished.
[0017] Preferably, in step S2, the adhesive is applied to the seed crystal support component and the AlN seed crystal wafer with a thickness of 5-5000 μm.
[0018] Preferably, in step S3, the low-temperature baking temperature is 50-200℃ and the baking time is 10-600min.
[0019] Preferably, in step S5, the negative pressure of the AlN seed wafer is 5-50 kPa, and the placement time is 1-24 h.
[0020] Preferably, in step S6, the heating temperature is 1000-1500℃ and the heating time is 1-10h.
[0021] This invention discloses a seed crystal bonding method for aluminum nitride crystal growth. To withstand the extremely high preparation temperature of high-quality aluminum nitride single crystals (>2200℃) and ensure that the main components do not interfere with the aluminum nitride growth process, aluminum nitride powder and tungsten powder are selected as the main components of the binder. Aluminum nitride has high temperature resistance and good bonding properties, while tungsten powder has a temperature resistance >3000℃, significantly improving the temperature resistance of the binder and ensuring high stability at high temperatures. Silicates have excellent lubricity and adhesion; therefore, the mixture of tungsten powder and aluminum nitride powder, supplemented by the strong bonding of silicates and distilled water, exhibits extremely high temperature resistance, adhesion, and high-temperature stability.
[0022] This invention discloses a seed crystal bonding method for aluminum nitride crystal growth. To increase the density and adhesion of the adhesive, and to reduce or eliminate porosity during aluminum nitride crystal growth, the method involves first exposing the crystal to a vacuum and baking it for a period of time after applying the adhesive. This pre-evaporation removes most of the moisture, as moisture is difficult to eliminate after bonding the seed crystal and support components, and can vaporize and backflow into the crystal during growth, forming pores. This is further supplemented by vacuum placement under negative pressure for a period of time to further eliminate moisture in the adhesive, effectively increasing the density of the adhesive and its bonding strength with the seed crystal and support components.
[0023] The present invention discloses a seed crystal bonding method for aluminum nitride crystal growth. To enhance the density and adhesion of the tungsten powder-doped binder, a high-temperature heating temperature (1000-1500℃) is used. This allows the tungsten powder, aluminum nitride powder, and silicate within the binder to fully bond at high temperature, resulting in extremely high density and adhesion. Heating temperatures below 1000℃ cannot achieve the preparation of a high-density binder with strong adhesion, and it is prone to detachment and the formation of voids during aluminum nitride growth.
[0024] The present invention discloses a seed crystal bonding method for aluminum nitride crystal growth. The adhesive is inexpensive, saves costs, is easy to obtain, easy to operate, and has obvious advantages in bonding effect.
[0025] The seed crystal bonding method for aluminum nitride crystal growth described in this invention is used for seed crystal bonding and fixation in high-temperature aluminum nitride crystal growth experiments and production. It can be kept at a high temperature of 2350℃ for more than 200 hours, which has significant advantages in the mass production of high-quality aluminum nitride single crystals and substrates. Attached Figure Description
[0026] Figure 1 The aluminum nitride seed wafer is bonded using the method described in Example 1 of this invention.
[0027] Figure 2 This refers to the aluminum nitride single crystal prepared by bonding aluminum nitride seed crystals using the method described in Example 1 of this invention. Detailed Implementation
[0028] The present invention will be further explained and described below with reference to the accompanying drawings and specific embodiments.
[0029] See Figure 1 The above is a flowchart illustrating the preparation process of a seed crystal bonding method for aluminum nitride crystal growth used in various embodiments of the present invention.
[0030] The seed crystal bonding process for aluminum nitride crystal growth is briefly described below through examples.
[0031] Example 1
[0032] S1: An adhesive is prepared by mixing aluminum nitride powder with a particle size of 1 μm, silicate, tungsten powder with a particle size of 1 μm, and distilled water in a certain proportion. The weight percentages of aluminum nitride powder, silicate, tungsten powder, and distilled water are 16%, 2%, 41%, and 41% respectively.
[0033] S2: The bonding surface of the support component is ground, and the bonding surface of the AlN seed wafer is chemically and mechanically polished. The support component material is tungsten block. The adhesive is evenly applied to the surface of the tungsten block and the AlN seed wafer, with adhesive thicknesses of 100μm and 100μm, respectively.
[0034] S3: Keep the tungsten block coated with adhesive and the AlN seed wafer exposed, and bake at 50°C for 500 minutes.
[0035] S4: Place the adhesive side of the AlN seed wafer on the adhesive side of the tungsten block.
[0036] S5: Place the bonded AlN seed wafers under a negative pressure of 10 kPa and leave them in a vacuum at room temperature for 20 hours.
[0037] S6: Place the AlN seed wafer and the tungsten block together in a high-temperature furnace, heat to 1100℃ for 10 hours, and then slowly cool to room temperature. Finally, the AlN seed wafer and the tungsten block are firmly bonded together.
[0038] Example 2
[0039] S1: An adhesive is prepared by mixing aluminum nitride powder with a particle size of 5 μm, silicate, tungsten powder with a particle size of 5 μm, and distilled water in a certain proportion. The aluminum nitride powder accounts for 15% by weight, the silicate accounts for 3% by weight, the tungsten powder accounts for 65% by weight, and the distilled water accounts for 17% by weight.
[0040] S2: The tungsten block bonding surface and the seed crystal bonding surface are processed according to the method in Example 1. The adhesive is uniformly applied to the surface of the tungsten block and the AlN seed crystal, respectively, with adhesive thicknesses of 500μm and 500μm.
[0041] S3: Keep the tungsten block coated with adhesive and the AlN seed wafer exposed, and bake at 100°C for 400 minutes.
[0042] S4: Place the adhesive side of the AlN seed wafer on the adhesive side of the tungsten block.
[0043] S5: Place the bonded AlN seed wafers under a negative pressure of 20 kPa at room temperature in a vacuum for 17 hours.
[0044] S6: Place the AlN seed wafer and the tungsten block together in a high-temperature furnace, heat to 1150℃ for 9 hours, and then slowly cool to room temperature. Finally, the AlN seed wafer and the tungsten block are firmly bonded together.
[0045] Example 3
[0046] S1: An adhesive is prepared by sequentially mixing aluminum nitride powder with a particle size of 6μm, silicate, tungsten powder with a particle size of 6μm, and distilled water in a certain proportion. The aluminum nitride powder accounts for 18% by weight, the silicate for 5% by weight, the tungsten powder for 45% by weight, and the distilled water for 32% by weight.
[0047] S2: The tungsten block bonding surface and the seed crystal bonding surface are processed according to the method in Example 1. The adhesive is uniformly applied to the surface of the tungsten block and the AlN seed crystal, respectively. The thickness of the adhesive applied to the two sides is 3000μm and 3000μm, respectively.
[0048] S3: Keep the tungsten block coated with adhesive and the AlN seed wafer exposed, and bake at 80°C for 400 minutes.
[0049] S4: Place the adhesive side of the AlN seed wafer on the adhesive side of the tungsten block.
[0050] S5: Place the bonded AlN seed wafers under a negative pressure of 25 kPa at room temperature in a vacuum for 13 hours.
[0051] S6: Place the AlN seed wafer and tungsten block together in a high-temperature furnace, heat to 1200℃ for 8 hours, and then slowly cool to room temperature. Finally, the AlN seed wafer and tungsten block are firmly bonded together.
[0052] Example 4
[0053] S1: An adhesive is prepared by sequentially mixing aluminum nitride powder with a particle size of 5 μm, silicate, tungsten powder with a particle size of 50 μm, and distilled water in a certain proportion. The aluminum nitride powder accounts for 15% by weight, the silicate for 4% by weight, the tungsten powder for 45% by weight, and the distilled water for 36% by weight.
[0054] S2: The bonding surface of the support component is polished, and the bonding surface of the AlN seed wafer is chemically and mechanically polished. The support component is made of tantalum block. The adhesive is evenly applied to the surfaces of the tantalum block and the AlN seed wafer, with adhesive thicknesses of 200μm and 200μm, respectively.
[0055] S3: Keep the tantalum block coated with adhesive and the AlN seed wafer exposed, and bake at 90°C for 350 minutes.
[0056] S4: Place the adhesive side of the AlN seed wafer on the adhesive side of the tantalum block.
[0057] S5: Place the bonded AlN seed wafers under a negative pressure of 30 kPa at room temperature in a vacuum for 12 hours.
[0058] S6: Place the AlN seed wafer and tantalum block together in a high-temperature furnace, heat to 1250℃ for 7 hours, and then slowly cool to room temperature. Finally, the AlN seed wafer and tantalum block are firmly bonded together.
[0059] Example 5
[0060] S1: An adhesive is prepared by sequentially mixing aluminum nitride powder (10 μm particle size), silicate, tungsten powder (20 μm particle size), and distilled water in a certain proportion. The aluminum nitride powder accounts for 10% by weight, the silicate for 3% by weight, the tungsten powder for 65% by weight, and the distilled water for 22% by weight.
[0061] S2: The tantalum block bonding surface and the seed crystal bonding surface are processed according to the method in Example 4. The adhesive is uniformly applied to the surface of the tantalum block and the AlN seed crystal, respectively, with adhesive thicknesses of 500μm and 500μm.
[0062] S3: Keep the tantalum block coated with adhesive and the AlN seed wafer exposed, and bake at 100°C for 300 minutes.
[0063] S4: Place the adhesive side of the AlN seed wafer on the adhesive side of the tantalum block.
[0064] S5: Place the bonded AlN seed wafers under a negative pressure of 35 kPa and vacuum at room temperature for 10 hours.
[0065] S6: Place the AlN seed wafer and tantalum block together in a high-temperature furnace, heat to 1350℃ for 6 hours, and then slowly cool to room temperature. Finally, the AlN seed wafer and tantalum block are firmly bonded together.
[0066] Example 6
[0067] S1: An adhesive is prepared by sequentially mixing aluminum nitride powder (15 μm particle size), silicate, tungsten powder (30 μm particle size), and distilled water in a certain proportion. The aluminum nitride powder accounts for 12% by weight, the silicate for 4% by weight, the tungsten powder for 50% by weight, and the distilled water for 34% by weight.
[0068] S2: The tantalum block bonding surface and the seed crystal bonding surface are processed according to the method in Example 4. The adhesive is uniformly applied to the surface of the tantalum block and the AlN seed crystal, respectively, with adhesive thicknesses of 1500um and 1500um.
[0069] S3: Keep the tantalum block coated with adhesive and the AlN seed wafer exposed, and bake at 120°C for 250 minutes.
[0070] S4: Place the adhesive side of the AlN seed wafer on the adhesive side of the tantalum block.
[0071] S5: Place the bonded AlN seed wafers under a negative pressure of 40 kPa and leave them in a vacuum at room temperature for 9 hours.
[0072] S6: Place the AlN seed wafer and tantalum block together in a high-temperature furnace, heat to 1400℃ for 5 hours, and then slowly cool to room temperature. Finally, the AlN seed wafer and tantalum block are firmly bonded together.
[0073] Example 7
[0074] S1: An adhesive is prepared by sequentially mixing aluminum nitride powder with a particle size of 8 μm, silicate, tungsten powder with a particle size of 25 μm, and distilled water in a certain proportion. The aluminum nitride powder accounts for 13% by weight, the silicate for 2% by weight, the tungsten powder for 55% by weight, and the distilled water for 30% by weight.
[0075] S2: The bonding surfaces of the boron nitride ceramic block and the seed crystal are processed according to the method in Example 4. The adhesive is uniformly applied to the surfaces of the boron nitride ceramic block and the AlN seed crystal, with adhesive thicknesses of 800 μm and 800 μm, respectively.
[0076] S3: Keep the adhesive-coated boron nitride ceramic block and AlN seed wafer exposed and bake at 160°C for 200 min.
[0077] S4: Place the adhesive side of the AlN seed wafer on the adhesive side of the boron nitride ceramic block.
[0078] S5: Place the bonded AlN seed wafers under a negative pressure of 45 kPa at room temperature in a vacuum for 8 hours.
[0079] S6: Place the AlN seed wafer and the boron nitride ceramic block together in a high-temperature furnace and heat at 1450℃ for 4 hours. Then slowly cool down to room temperature. Finally, the AlN seed wafer and the boron nitride ceramic block are firmly bonded together.
[0080] Example 8
[0081] S1: An adhesive is prepared by sequentially mixing aluminum nitride powder (20 μm particle size), silicate, tungsten powder (45 μm particle size), and distilled water in a certain proportion. The aluminum nitride powder accounts for 10% by weight, the silicate for 4% by weight, the tungsten powder for 60% by weight, and the distilled water for 26% by weight.
[0082] S2: The bonding surfaces of the boron nitride ceramic block and the seed crystal are processed according to the method in Example 4. The adhesive is uniformly applied to the surfaces of the boron nitride ceramic block and the AlN seed crystal, respectively, with adhesive thicknesses of 2000 μm and 2000 μm.
[0083] S3: Keep the adhesive-coated boron nitride ceramic block and AlN seed wafer exposed and bake at 180°C for 150 min.
[0084] S4: Place the adhesive side of the AlN seed wafer on the adhesive side of the boron nitride ceramic block.
[0085] S5: Place the bonded AlN seed wafers under a negative pressure of 50 kPa at room temperature in a vacuum for 7 hours.
[0086] S6: Place the AlN seed wafer and the boron nitride ceramic block together in a high-temperature furnace, heat to 1500℃ for 3 hours, and then slowly cool to room temperature. Finally, the AlN seed wafer and the boron nitride ceramic block are firmly bonded together.
[0087] Application Example 1
[0088] The aluminum nitride seed wafer and tungsten sheet were bonded and cured using the method described in Example 1 (see Example 1). Figure 1 The bonded seed wafers were assembled onto the top of the growth chamber for physical vapor transport (PVT) aluminum nitride single crystal growth, ultimately producing high-quality, pore-free AlN single crystals (see...). Figure 2 This solution, when applied to actual mass production, significantly improved substrate yield and structural quality, and effectively reduced production costs.
[0089] Application Example 2
[0090] This application example tested the performance of the bonded seed wafers from the above embodiments in extreme high-temperature applications. The bonded seed wafers from each embodiment were placed at temperatures of 2200℃, 2250℃, 2300℃, and 2350℃ for extended periods. The test results showed that the bonded seed wafers from each embodiment could maintain their bonded state for over 200 hours at these temperatures. The bonding stability maintained by the bonding process of this invention has significant advantages in the mass production of high-quality aluminum nitride single crystals and substrates.
[0091] The above description of the embodiments is only for the purpose of helping to understand the method and core ideas of the present invention. It should be noted that those skilled in the art can make several improvements and modifications to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the protection scope of the claims of the present invention.
Claims
1. A method for seed crystal bonding in aluminum nitride crystal growth, characterized in that, Includes the following steps: S1: Mix aluminum nitride powder, silicate, tungsten powder and distilled water in a certain proportion to make an adhesive; S2: Apply the adhesive evenly to the bonding surfaces of the support component and the AlN seed wafer respectively; S3: Expose the bonding surfaces of the support component coated with the adhesive and the AlN seed wafer, and bake at a low temperature for a period of time; S4: Place the bonding surface of the AlN seed wafer on the bonding surface of the support component; S5: Place the bonded AlN seed wafer and support components under a certain negative pressure and at room temperature in a vacuum for a period of time; S6: The bonded AlN seed wafer and support component are placed in a high-temperature furnace and heated in an inert gas atmosphere for a period of time, then slowly cooled to room temperature, and finally the AlN seed wafer and the support component are firmly bonded together.
2. The seed crystal bonding method for aluminum nitride crystal growth according to claim 1, characterized in that: The aluminum nitride powder in step S1 has a particle size of 0.5-20 μm, and the tungsten powder has a particle size of 1-50 μm.
3. The seed crystal bonding method for aluminum nitride crystal growth according to claim 1, characterized in that: In step S1, the aluminum nitride powder accounts for 10-20% by weight, the silicate accounts for 1-5% by weight, the tungsten powder accounts for 40-70% by weight, and the distilled water accounts for 10-50% by weight.
4. The seed crystal bonding method for aluminum nitride crystal growth according to claim 1, characterized in that: In step S2, the support component is made of any one of the following high-temperature resistant materials: tungsten, tantalum, molybdenum, tungsten carbide, tungsten nitride, tantalum carbide, tantalum nitride, and boron nitride.
5. The seed crystal bonding method for aluminum nitride crystal growth according to claim 1, characterized in that: In step S2, the bonding surface of the support component is ground or polished, and the bonding surface of the AlN seed wafer is chemically and mechanically polished.
6. The seed crystal bonding method for aluminum nitride crystal growth according to claim 1, characterized in that: In step S2, the adhesive is applied to the bonding surfaces of the support component and the AlN seed wafer with a thickness of 5-5000 μm.
7. The seed crystal bonding method for aluminum nitride crystal growth according to claim 1, characterized in that: In step S3, the low-temperature baking temperature is 50-200℃, and the baking time is 10-600min.
8. The seed crystal bonding method for aluminum nitride crystal growth according to claim 1, characterized in that: In step S5, the negative pressure of the AlN seed wafer is 5-50 kPa, and the placement time is 1-24 h.
9. The seed crystal bonding method for aluminum nitride crystal growth according to claim 1, characterized in that: In step S6, the heating temperature is 1000-1500℃ and the heating time is 1-10h.
Citation Information
Patent Citations
Seed crystal bonding method for aluminum nitride single crystal growth
CN109487335A
High-temperature bonding method for aluminum nitride seed crystals
CN113668065A